2007
DOI: 10.2463/mrms.6.199
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of RF Heating on SAR and Implant Position in a 1.5T MR System

Abstract: Purpose: We evaluated radiofrequency (RF) heating of a humerus implant embedded in a gel phantom during magnetic resonance (MR) imaging for the speciˆc absorption rate (SAR), angle between the implant and static magneticˆeld (B 0 ), and position of the implant in the irradiation coil.Methods: We embedded a stainless steel humerus implant 2 cm deep in tissue-equivalent loop and mass phantoms, placed it parallel to the static magneticˆeld of a 1.5T MR scanner, and recorded the temperatures of the implant surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 19 publications
6
48
1
Order By: Relevance
“…More recently, Tagliati et al (2009) reported that 3,304 DBS patients had brain MRI at 40 centers responding to a questionnaire. Despite many centers reporting use of postoperative brain MRI, including use of the SP, V, or VP platforms (Duffner, Schiffbauer, Breit, Friese, & Freudenstein, 2002;Elias, Fu, & Frysinger, 2007;Hamid et al, 2005;Larson et al, 2008;Mehdorn et al, 2005;Pillon et al, 2000;Pollo et al, 2007;Schrader, Hamel, Weinert, & Mehdorn, 2002), as well as series involving 100 or more DBS leads (Benabid et al, 2002;Elias et al, 2007;Funkiewiez et al, 2004;Goodman et al, 2006;Hemm et al, 2005;Larson et al, 2008;Mehdorn et al, 2005;Oh, Abosch, Kim, Lang, & Lozano, 2002;Umemura et al, 2003) including the body weight entered, sequence parameters, and also by the specific object within the field as well as the precise location and positioning of the object in the field Mattei et al, 2008;Muranaka et al, 2007). For example, displayed SAR H is increased in our experience for a given patient in the setting of a stereotactic head ring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Tagliati et al (2009) reported that 3,304 DBS patients had brain MRI at 40 centers responding to a questionnaire. Despite many centers reporting use of postoperative brain MRI, including use of the SP, V, or VP platforms (Duffner, Schiffbauer, Breit, Friese, & Freudenstein, 2002;Elias, Fu, & Frysinger, 2007;Hamid et al, 2005;Larson et al, 2008;Mehdorn et al, 2005;Pillon et al, 2000;Pollo et al, 2007;Schrader, Hamel, Weinert, & Mehdorn, 2002), as well as series involving 100 or more DBS leads (Benabid et al, 2002;Elias et al, 2007;Funkiewiez et al, 2004;Goodman et al, 2006;Hemm et al, 2005;Larson et al, 2008;Mehdorn et al, 2005;Oh, Abosch, Kim, Lang, & Lozano, 2002;Umemura et al, 2003) including the body weight entered, sequence parameters, and also by the specific object within the field as well as the precise location and positioning of the object in the field Mattei et al, 2008;Muranaka et al, 2007). For example, displayed SAR H is increased in our experience for a given patient in the setting of a stereotactic head ring.…”
Section: Discussionmentioning
confidence: 99%
“…Specific absorption rate (SAR) is defined as the RF power absorbed per unit mass of an object (International Electrochemical Commission (IEC) Standard 60601-2-33, 2004). A linear relationship between SAR and DBS lead-contact heating has been suggested in laboratory models (Baker, Tkach, Phillips, & Rezai, 2006;Muranaka et al, 2007). Routine brain imaging employs scans with SAR H values up to 30 times greater than the SAR H recommended in manufacturer guidelines in the setting of implanted DBS hardware (IEC Standard 60601-2-33, 2004;U.S.…”
Section: Introductionmentioning
confidence: 99%
“…These results were previously reported. 22 Comparison of RF heating between 1.5-and 3.0-T MR systems…”
Section: Dependence Of Rf Heating On Displacementmentioning
confidence: 99%
“…Highest temperature increases were reported at tips of straight metallic wires [4][5][6][7][8]. Particular concern was also raised with regard to implanted metallic loops [9]. The diverging results demonstrate the need for case-by-case risk assessment.…”
Section: Introductionmentioning
confidence: 97%